Jesse Jackson for President Rally at Warnor's Theatre - Watkins, Howard::::::::: (1984)
Full stage view of Jesse Jackson speaking at microphone; seated: ?, Chris Petersen, Lorri Foster, Lily Gonzales, Barbara Gaines, Pauline Kimber, Ben Benavidez, ? Arturo Vasques, ?